2015
DOI: 10.15376/biores.10.2.3364-3377
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Polyvinyl Alcohol-Based Composite Reinforced with Nanocellulose and Nanosilica

Abstract: This work reported the thermomechanical and morphological properties of polyvinyl alcohol (PVA) nanocomposites reinforced with nanosilica and oil palm empty fruit bunches derived nanocellulose. The nanocomposites were characterized by mechanical, thermal, XRD, optical, and morphological studies. Uniformity dispersion of the nanofillers at a 3 wt% concentration has been shown by scanning electron microscopy, whereas the changes in crystallinity were demonstrated by X-ray diffraction analysis. Addition of nanosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(72 citation statements)
references
References 40 publications
(40 reference statements)
3
69
0
Order By: Relevance
“…There is an optimal density of NFC that can enhance strength and modulus without sacrifice toughness of nanocomposites. Researchers have suggested that the optimal content could vary from 3 wt% to 5 wt% approximately [45,46]. That is the reason why the content of NFC is fixed at 3 wt% in this work.…”
Section: Preparation Of Pva/nfc/rgo Nanocomposite Filmsmentioning
confidence: 99%
“…There is an optimal density of NFC that can enhance strength and modulus without sacrifice toughness of nanocomposites. Researchers have suggested that the optimal content could vary from 3 wt% to 5 wt% approximately [45,46]. That is the reason why the content of NFC is fixed at 3 wt% in this work.…”
Section: Preparation Of Pva/nfc/rgo Nanocomposite Filmsmentioning
confidence: 99%
“…Both peaks at 1210 and 1293 cm -1 were attributed to the OH bending vibrations of cellulose (Siyamak et al 2012). The peak at 1755 cm -1 was attributed to the stretching of C=O of lignin Ching et al 2015). The significant peaks of OPEFB fibers were not observed in the fiber-reinforced PLA composites because they may have been covered by other strong peaks of PLA, given that the amount of fibers was minimal compared to that of the PLA polymer matrix.…”
Section: Characterizationmentioning
confidence: 99%
“…Composites can be produced with the view of tailoring physical, chemical, or mechanical properties, to fulfil the requirements of different applications such as automotive, packaging, aeronautic, naval, and so on [48,49]. …”
Section: Biocomposite Materialsmentioning
confidence: 99%